Fenestrated A1 in Ruptured Anterior Communicating Artery Aneurysm: A Case Report - Nepal, Pankaj Raj; Thapa, Dinesh Kumar; Bhattrai, Robin; Rajbanshi, Jagat Narayan (Eastern Green Neurosurgery, 2020)
There is a lot of variation around the anterior communicating artery (Acom) and various classification systems have been quoted many times in literatures. Here we have reported a rare case of a 52-year-old woman who had ruptured Acomartery aneurysm. The angiography also showed a fenestration of the A1 segment of anterior cerebral artery.